Implementation of the Electronic Document Management System in Joint Services Council for Irbid Governorate - Aljamrh, Malek Mohammed Kalil (Journal of Economic, Administrative and Legal Sciences, 2023)
An electronic document management system (EDMS) is a software program that manages the creation, storage, and control of documents electronically. The new electronic document management system should include different types of incoming and outgoing documents while ensuring safe access to data in the system where the project identified additional steps and procedures applied to the current EDMS method to make sure that it covers the whole process of creating for a new system Joint Services Council (JSC) for Irbid Governorate as designing new EDMS through using Rich picture technique and Strategic quadruple SWOT analysis then updating Rich picture diagrams of the new system where the proposed framework is applied to an EDMS to demonstrate how the method can be used practice the framework evaluated recommendations for further research are suggested.